Psychosocial deprivation in women with gestational diabetes mellitus is associated with poor fetomaternal prognoses: an observational study. Issue 3 (6th March 2015) - Cosson, Emmanuel; Bihan, Hélène; Reach, Gérard; Vittaz, Laurence; Carbillon, Lionel; Valensi, Paul
Abstract : Objective: To evaluate the prognoses associated with psychosocial deprivation in women with gestational diabetes mellitus (GDM). Design: Observational study considering the 1498 multiethnic women with GDM who gave birth between January 2009 and February 2012. Setting: Four largest maternity units in the northeastern suburban area of Paris. Participants: The 994 women who completed the Evaluation of Precarity and Inequalities in Health Examination Centers (EPICES) questionnaire. Main outcome measure: Main complications of GDM (large infant for gestational age (LGA), shoulder dystocia, caesarean section, pre-eclampsia). Results: Psychosocial deprivation (EPICES score ≥30.17) affected 577 women (56%) and was positively associated with overweight/obesity, parity and non-European origin, and negatively associated with family history of diabetes, fruit and vegetable consumption and working status. The psychosocially deprived women were diagnosed with GDM earlier, received insulin treatment during pregnancy more often and were more likely to have LGA infants (15.1% vs 10.6%, OR=1.5 (95% CI 1.02 to 2.2), p<0.05) and shoulder dystocia (3.1% vs 1.2%, OR=2.7 (0.97 to 7.2), p<0.05). In addition to psychosocial deprivation, LGA was associated with greater parity, obesity, history of GDM, ethnicity, excessive gestational weight gain and insulin therapy. A multivariate analysis using these covariates revealed that the EPICES score was independently associated with LGA infants (per 10 units, OR=1.12 (1.03 to 1.20), p<0.01). Conclusions: In our area, psychosocial deprivation is common in women with GDM and is associated with earlier GDM diagnoses and greater insulin treatment, an increased likelihood of shoulder dystocia and, independently of obesity, gestational weight gain and other confounders with LGA infants.